2019
DOI: 10.15666/aeer/1706_1343513453
|View full text |Cite
|
Sign up to set email alerts
|

Diet Influences the Accumulation of Short-Chain Fatty Acids Associated With the Gut Microbiota in the Grass Carp (Ctenopharyngodon Idellus) Hindgut

Abstract: Diet changes the composition and function of the gut microbiota (GM). Short-chain fatty acids (SCFAs) are mainly produced through carbohydrate fermentation by the GM. It remains unclear whether changing the diet influences the accumulation of SCFAs in the grass carp (Ctenopharyngodon idellus) gut. To address this question, we compared SCFA accumulation with GM changes in the hindgut contents of grass carp in groups fed hybrid giant napier (Pennisetum sinese Roxb, HG), formula feed (FG), and broad bean (Vicia f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 69 publications
(110 reference statements)
0
2
0
Order By: Relevance
“…The enhancement of the intestinal antioxidant system by dietary NSPs may be related to their fermentation products. To our knowledge, dietary NSPs can be fermented by intestinal flora to produce large amounts of short-chain fatty acids (SCFAs) [ 4 , 16 , 50 ]. Furthermore, recent studies showed that dietary supplementation with SCFAs activated the zebrafish intestinal antioxidant defence system, including an increase in the activity of SOD, CAT and glutathione peroxidase [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The enhancement of the intestinal antioxidant system by dietary NSPs may be related to their fermentation products. To our knowledge, dietary NSPs can be fermented by intestinal flora to produce large amounts of short-chain fatty acids (SCFAs) [ 4 , 16 , 50 ]. Furthermore, recent studies showed that dietary supplementation with SCFAs activated the zebrafish intestinal antioxidant defence system, including an increase in the activity of SOD, CAT and glutathione peroxidase [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the main method of aquaculture in China is intensive aquaculture, which has the advantage of increasing the output of aquatic products and profits (Edwards, 2015). However, owing to the high stocking density of aquatic animal and large amount of feed input, the discharge of aquaculture wastewater (AW) causes eutrophication, hypoxia, and other adverse effects on the natural water environment (Li et al, 2019). Therefore, efficient treatment OPEN ACCESS EDITED BY of pollutants in AW is necessary to ensure the sustainable development of the aquaculture industry.…”
Section: Introductionmentioning
confidence: 99%